A Study Of An Error Analysis In Simple Past Tense In Teaching Writing - Maulana Yusuf Aditya (STABN RADEN WIJAYA WONOGIRI, 2020)
An error anaysis has an important role to reveal what kinds of error the student do most, to know the causes of the error and how the student can learn from their mistakes in writing by themselves. Writing Ability always have main concern when the student created written text. Writing ability had been good result if the grammar was perfect. The pupose of this study is To know the error when the student make in simple past tense in teaching writing Recount Text At Eight Grade In SMP Al-Baisuny. The research design that was used in this study is qualitative research. The object of this study was the eight grade students of SMP AL-Baisuny which consists of 25 students In this research, the instruments used was: Student’s Worksheet. The result of the analysis shows that: (1) the errors in recount writing made by the eight grade students of SMP Al-Baisuny are 82 occurrences of all errors. In term of each type errors, the errors of Overgeneralization 25 times, errors of Ignorance of Rules Restriction 22 times, errors of Incomplete Application of Rules 21 times, and errors of False Concept Hypothesis 14 times. Finally, it is hoped that the teacher would make use of those findings in their teaching learning process in order to minimize the students’ errors.